Development as a key evaluative concept of spatial system transformation - Leksin, Vladimir N. (Baltic Region, 2024)
This article examines the spatial socioeconomic development problems that have emerged prominently in Russia in recent years. A special focus is the notion of 'razvitie' (development) gaining mainstream traction in the vocabulary of Russian politicians, researchers and media professionals. Authoritative scholarly opinions are cited, describing development as a process of changes in objects and phenomena without implying a positive connotation. Using the example of external regulation of anthropogenic spatial systems, it is shown that development should enhance the stability of the systems' functioning, considering their equifinality and potential for self-organisation (self-development). A genetic connection is established between the concept of 'spatial development' and the global advances in economic geography. Attention is paid to the features of spatial and regional development as strategic planning objects. The article also examines the feasibility of accurately assessing the outcomes of a spatial development strategy by quantifying the achievement of its goals and targets. It is emphasised that results highlighting regional disparities and settlement patterns should be compared within groups of similar regions and macro-regions, such as northern, central and southern provinces of European Russia, Siberian territories, the Far East, the Arctic Zone and the republics of the North Caucasus. For demographic processes, comparisons should be based on specific population groups: children, youth, the working-age population, pensioners and migrants. Specific changes in productive forces distribution that align with target indicators should be verified by population assessments based on annual surveys.